BIDDER VALUE IMPLICATIONS OF CROSS-BORDER VS DOMESTIC ACQUISITIONS: A STUDY OF DUTCH FIRMS - Hidayat W H, Ramadhan
This study aims to investigate the value implications of cross-border as well as domestic acquisitions which are undertaken by Dutch bidding firms. This study focuses on Dutch firms since the Netherlands is one of the world’s largest sources of cross-border investments, and cross-border acquisitions are a prime example. Past literature which focuses on different regions/countries discovered conflicting findings regarding value implications of cross-border and domestic acquisitions. Some recorded results which pointed towards value creation for cross-border acquisitions while some found the opposite. This study utilizes the event study methodology to find out whether cross-border and domestic acquisitions create significant value right after the announcement of the acquisition. This is done by testing the significance of the cumulative average abnormal returns (CAARs) of 62 cases of acquisitions, comprised of 31 cross-border and domestic acquisitions, all involving a Dutch bidding firm. The significance tests yielded statistically insignificant results for all the groups of samples. However, the CAARs themselves were positive for the cross-border acquisitions and also positive but lower for domestic acquisitions. The unexpected results led to the conclusion that there is weak support towards the value creating nature of cross-border acquisitions and that engaging in a domestic acquisition instead also does not guarantee value creation, while further inspection discovered that the firms’ strategy may also play a role in the Dutch acquisition’s value creation.